The Malaysia Plan : A Policy Initiative and/or a Shopping List - Dick Lembang, Dugun; Lucy, Sebli; Stanley Bye, Kadam-Kiai (UNIMAS Publisher, 2025)
The Malaysia Plan, a cornerstone of national development strategy, is designed to guide economic and social progress through five-year planning cycles. Many countries implemented the five-year development plan because of the failure of the market or price mechanism to promote growth, efficiency and equity. The plan can help to accelerate the country’s economic growth and development through resource mobilization and allocation. However, its effectiveness has been increasingly questioned due to persistent gaps between policy formulation and implementation. The process of making a Malaysia Plan is a lengthy exercise, involving all levels of the civil service, and numerous technical committees and taskforces. This paper critically examines whether the Malaysia Plan functions as a coherent policy initiative or merely a political shopping list. Drawing on document analysis and case-based evidence from Sarawak—specifically the Kuching Outer Ring Road and Samarahan projects—the study explores how institutional fragmentation, shifting political priorities, and budgetary constraints undermine project execution. The analysis is framed within institutionalism theory, revealing that over 60% of approved projects are not completed within the plan period. These findings suggest that the Malaysia Plan, while ambitious in scope, often fails to translate strategic objectives into actionable outcomes. The paper concludes with recommendations for enhancing institutional accountability, improving project selection transparency, and aligning budgetary processes with long-term planning goals.